Effect of antenatal retroviral therapy on feto-maternal outcome in human immunodeficiency virus seropositive patients - Trivedi, Swati; Nagar, Oby; Trivedi, Shashank; Rastogi, Prasoon (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To study the effect of HIV and duration of ART on term of delivery, newborn birth weight and adverse fetal outcomes. Methods: Prospective comparative study of 40 HIV seropositive pregnant females with varying duration of ART (tenofovir 300 mg + lamivudine 300 mg + efavirenz 600 mg) and HIV seronegative pregnant females attending ANC and delivering in department of obstetrics and gynecology at S. M. S. Medical College, Jaipur, Rajasthan, India. Results: Most HIV seropositive patients were in age group 25 to 30 years and more number were booked in comparison to unbooked. Adverse fetal outcomes were seen more in HIV seropositive patients and they were found to be statistically significant (p=0.029). No relationship could be derived of duration of ART on either the birth weight or term of delivery or adverse fetal outcomes. Conclusions: Maternal HIV infection was significantly found associated with adverse fetal outcome and this was not affected by the use of ART.